MEDICATION SAFETY PRACTICES THROUGH DRUG RELATED PROBLEMS (DRPs) REPORTING AT BETHESDA HOSPITAL, YOGYAKARTA - Dewi Dewi; L Endang Budiarti; Iwan Dwiprahasto (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Identification of problems caused by the use of drugs, followed by corrective actions, treatment, and prevention are essential to ensure safety. Implementation of medication error reporting systems as well as providing recommendations by pharmacists are strategies to improve medication safety practices in the health care system. A quasi experimental study was conducted at two surgical wards in Yogyakarta Bethesda Hospital. Clinical pharmacist did the identification, corrective actions, as well as reporting of the medication errors (MEs) incidents in both wards. A total of 283 drug problems at Ward I and 39 drug problems at Ward II were identified by clinical pharmacists. All of ME incidents identified at Ward II and 13,5 of those at Ward I were reported through pharmacy’s reporting system. Nineteen DRPs at Ward I and 13 DRPs at Ward II were resolved through communication and delivering recommendations to physicians. A total of 26,3% of written recommendations were accepted compared with 84,6% of verbal recommendations (p = 0,02). All of the DRPs resolved by verbal communication, whereas only 33,3% of those resolved by written communication. Keywords: medication safety practices, medication errors, Drug Related Problems, reporting